2009
DOI: 10.1063/1.3275758
|View full text |Cite
|
Sign up to set email alerts
|

Hole-based memory operation in an InAs/GaAs quantum dot heterostructure

Abstract: We present an InAs/GaAs quantum dot ͑QD͒ memory structure with all-electrical data access which uses holes as charge carriers. Charging and discharging of the QDs are clearly controlled by a gate voltage. The stored information is read-out by a two-dimensional hole gas underneath the QD-layer. Time resolved drain-current-measurements demonstrate the memory operation. Present write times are 80 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Fast carrier capture and long charge storage capabilities of type-II QDs suggest their potential application in memory devices. 1,2 Recent studies have shown that the use of a two-dimensional electron 3,4 or hole 5,6 gas in combination with QDs allows writing and reading information, demonstrating the basic operations required in memory devices.…”
mentioning
confidence: 99%
“…Fast carrier capture and long charge storage capabilities of type-II QDs suggest their potential application in memory devices. 1,2 Recent studies have shown that the use of a two-dimensional electron 3,4 or hole 5,6 gas in combination with QDs allows writing and reading information, demonstrating the basic operations required in memory devices.…”
mentioning
confidence: 99%
“…Furthermore, QDs are very promising for memory units with nano-scale feature sizes. The feasibility of such a QD-based Flash memory has been demonstrated recently [6,7]. In this paper, we study the coupling between self-organized InAs/GaAs QDs and an adjacent two-dimensional hole gas (2DHG) at temperatures ranging from 4 K to 100 K. Capacitance-voltage (C-V) measurements and time-resolved measurements of the source-drain current in the 2DHG reveal the discrete electronic structure of the InAs/GaAs QDs and give access to the many-particle hole states of the QD ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…The use of quantum dots (QDs) in semiconductor devices such as laser, photodetector, and future dynamic memories [1], requires a detailed understanding of the physical properties determining the exchange of charge carriers between the QDs and the host material. Moreover, the efficiency of luminescence from QD laser structures depends on the capture of carriers within the QDs and the minimisation of non-radiative recombination channels within the QD and the surrounding matrix via defects at heterointerfaces [2].…”
Section: Introductionmentioning
confidence: 99%